Samuel Beckett and BBC Radio
XV, 308 p.
Keywords: This book is the first sustained examination of Samuel Beckett’s pivotal engagements with post-war BBC radio. The BBC acted as a key interpreter and promoter of Beckett’s work during this crucial period of his "getting known" in the Anglophone world in the 1950s and 1960s, especially through the culturally ambitious Third Programme, but also by the intermediary of the house magazine, The Listener. The BBC ensured a sizeable but also informed reception for Beckett’s radio plays and various “adaptations” (including his stage plays, prose, and even poetry); the audience that Beckett's works reached by radio almost certainly exceeded in size his readership or theatre audiences at the time. In rethinking several key aspects of his relationship with the BBC, a mix of new and familiar Beckett critics take as their starting point the previously neglected BBC radio archives held at the Written Archive Centre in Caversham, Berkshire. The results of this extended reassessment are timely and, in many cases, quite surprising for readers of Beckett and for scholars of radio, “late modernism,” and post-war British culture more broadly.